2016
DOI: 10.1142/s0217751x16501839
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Casimir densities for a cylindrical shell on de Sitter space

Abstract: Complete set of cylindrical modes is constructed for the electromagnetic field inside and outside a cylindrical shell in the background of (D + 1)-dimensional dS spacetime. On the shell, the field obeys the generalized perfect conductor boundary condition. For the Bunch-Davies vacuum state, we evaluate the expectation values (VEVs) of the electric field squared and of the energy-momentum tensor. The shell-induced contributions are explicitly extracted. In this way, for points away from the shell, the renormali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…the latter equation is reduced to ∂ l (rA l ) = 0 and coincides with the corresponding equation in the Minkowski bulk. The procedure to find the complete set of solutions to the Maxwell equations is similar to that we have already described in [18] for the bulk in the absence of the cosmic string. The only difference is in the periodicity condition along the azimuthal direction φ.…”
Section: Cylindrical Electromagnetic Modesmentioning
confidence: 99%
“…the latter equation is reduced to ∂ l (rA l ) = 0 and coincides with the corresponding equation in the Minkowski bulk. The procedure to find the complete set of solutions to the Maxwell equations is similar to that we have already described in [18] for the bulk in the absence of the cosmic string. The only difference is in the periodicity condition along the azimuthal direction φ.…”
Section: Cylindrical Electromagnetic Modesmentioning
confidence: 99%
“…It has been shown that the influence of the gravitational field on the local characteristics of the vacuum state is essential at distance from the boundaries larger than the curvature radius of the background geometry. The VEVs of the field squared and energy-momentum tensor for scalar and electromagnetic fields induced by a cylindrical boundary in dS bulk have been investigated in [22,23]. Another class of exactly solvable problems correspond to spherical boundaries.…”
Section: Introductionmentioning
confidence: 99%